1992
DOI: 10.1096/fasebj.6.15.1281458
|View full text |Cite
|
Sign up to set email alerts
|

The Src family of tyrosine protein kinases in hemopoietic signal transduction

Abstract: The Src family of tyrosine protein kinases represent an expanding class of closely related intracellular enzymes that participate in the signal transduction pathways of a variety of surface receptors. One of the more surprising aspects of the information relating Src protein kinases to receptor signaling is the apparent diversity of receptor types with which the Src-related enzymes are reported to interact physically or functionally. Traditional biochemical and genetic approaches have yielded much information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
135
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 2 publications
(2 reference statements)
4
135
0
Order By: Relevance
“…Like other Src family kinases, Lck contains a C-terminal kinase domain, a single Src homology 2 (SH2) and SH3 domain, and an N-terminal region that is distinct from other family members (26). SH3 domains are able to mediate protein interactions by binding certain proline-rich amino acid sequences (27,28), and a number of proteins have been reported to bind the Lck SH3 domain including c-Cbl, PI-3-K, Ras-GAP, HS1, and CD2 (29 -33).…”
Section: Activation Of T-lymphocytes Is Initiated By Engagement Of Thmentioning
confidence: 99%
“…Like other Src family kinases, Lck contains a C-terminal kinase domain, a single Src homology 2 (SH2) and SH3 domain, and an N-terminal region that is distinct from other family members (26). SH3 domains are able to mediate protein interactions by binding certain proline-rich amino acid sequences (27,28), and a number of proteins have been reported to bind the Lck SH3 domain including c-Cbl, PI-3-K, Ras-GAP, HS1, and CD2 (29 -33).…”
Section: Activation Of T-lymphocytes Is Initiated By Engagement Of Thmentioning
confidence: 99%
“…These enzymes have been implicated in signal-transduction pathways, and Lyn, which is expressed in a wide range of tissues and cell types, has been shown to physically and functionally associate with various receptor molecules and, therefore, to be localized at the cell membrane [37]. It has been suggested that, as a consequence of their localization, the Src family tyrosine kinases may be accessible to distinct regulatory proteins and substrates.…”
Section: Discusslonmentioning
confidence: 99%
“…The Src family consists of nine related protein tyrosine kinases that participate in signaling from cell surface receptors to the interior of the cell (reviewed in Cantley et al, 1991;Bolen et al, 1992). All members of the Src family are covalently modified by the 14-carbon fatty acid myristate.…”
Section: Introductionmentioning
confidence: 99%